2016
DOI: 10.14746/ssllt.2016.6.2.7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of CLIL on mathematical content learning: A longitudinal study

Abstract: Previous research has shown that content and language integrated learning (CLIL), an educational approach that offers content courses through more than one educational language, increases metalinguistic awareness. This improved insight into language structures is supposed to extend beyond the linguistic domain. In the present study, the question whether pupils who learn in a CLIL environment outperform their traditionally schooled peers in mathematics is investigated. In total, 107 pupils entered the study. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 32 publications
(40 reference statements)
0
28
0
5
Order By: Relevance
“…Compared to studies on language learning, those on content learning have been less conclusive. For instance, Surmont, Struys, Van Den Noort, and Van De Craen (2016) examined the effect of French-medium CLIL on pupils' learning of mathematics and found that CLIL pupils (n = 35) outperformed their non-CLIL peers (n = 72) already after three months. The pre-test showed that there were no a priori differences between the two groups.…”
Section: Learning Outcomes In Clilmentioning
confidence: 99%
“…Compared to studies on language learning, those on content learning have been less conclusive. For instance, Surmont, Struys, Van Den Noort, and Van De Craen (2016) examined the effect of French-medium CLIL on pupils' learning of mathematics and found that CLIL pupils (n = 35) outperformed their non-CLIL peers (n = 72) already after three months. The pre-test showed that there were no a priori differences between the two groups.…”
Section: Learning Outcomes In Clilmentioning
confidence: 99%
“…The positive impact of the CLIL on the mathematical performance of pupils was identified even after a short period of time [13]. Therefore teaching specialist subjects in a foreign language represents the beneficial space for the unification of a language and professional knowledge in a particular subject [10].…”
Section: Resultsmentioning
confidence: 99%
“…How can, in practice, L2 learners and teachers make use of these advantages and, at the same time, take better into account the disadvantages of being bilingual? A recent study by Surmont and colleagues [124], for instance, found that teaching content courses through more than one educational language increased meta-linguistic awareness. The fact that the pupils improved in mathematics more than those who had only been taught in their native language showed that this improved insight extends beyond the linguistic domain.…”
Section: General Limitations Of Studies Conducted So Farmentioning
confidence: 98%